Online travel data: A goldmine of new opportunities - Garrow, Laurie; Luken, Brittany (Henry Stewart Talks, 2009)
Development needs triggered by the internet, Low cost carriers, Research opportunities, Revenue management (RM) applications, 'Choice-based' models, Under forecasting of chosen alternatives, New market segmentation, One way pricing opportunities, Recapture rate modeling, Itinerary choice applications